Immobilizing polyiodides with expanded Zn2 channels for high-rate practical zinc-iodine battery - Wu, Jiawen (2024)
Aqueous zinc-iodine battery (AZIB) has the advantage of low cost and high specific capacity but suffer from the soluble polyiodides shuttling and sluggish redox kinetics. Herein, these two limitations are addressed by employing a cathode additive (zirconium hydrogen phosphate, denoted as EI-ZrP) which provides dual functions: an agent for polyiodide confinement, and abundant channels for zinc ion transport. An enlarged crystalline interlayer (from typical 7.5 to 18.3 Å) of the EI-ZrP significantly enhances the ionic conductivity and simultaneously immobilizes polyiodides, leading to an accelerated conversion process. AZIB with EI-ZrP in the iodine cathode exhibits a high capacity retention over 10,000 cycles (with a 0.02‰ decay rate per cycle). Quasi-solid-state Zn-I2 pouch cell has been constructed using hydrogel-paper as separator and EI-ZrP additive, which delivers a high areal capacity under repeated bending. As a proof-of-concept demonstration, the paper battery is integrated to power a wireless flexible pressure sensor system (WFPSS). This strategy may shed light on the rational design of conversion-type cathode materials for both energy storage and flexible portable electronics.